A física na formação de tecnólogos - Gneiding, Ivan Meskauskas (2010)
This work reports a study which investigated the role and importance of Physics in Technology Undergraduate Programs, being based on the Curitiba Campus of the Federal University of Technology - Paraná (UTFPR), an institution considered a point of reference in technical and technological education in Brazil. Starting from the premise that Physics has a large importance in, at least, providing technical and scientific basis for the students, but also that it can have a fundamental role in general formation, this research intended to show the relations between Physics and the formation of technical personnel in the investigated programs. Underlain by the works of Celso Suckow da Fonseca, Luiz Antônio Cunha e Nilson Marcos Dias Garcia, this research sought to evidence, through a documental investigation, the presence of Physics concepts in teaching proposals of professional formation schools, from the Schools of Artifice Apprentices up to the emerging of technological teaching in undergraduate programs. Taking as sources the official documents of UTFPR and testimonies conceded in interviews with coordinators and professors of this institution, it was possible to show and analyze, at the current moment, the presence of Physics in the investigated programs, as well as to analyze the context in which it is inserted, its importance and its roles in each one of them. The results showed that Physics concepts are a lot more present than what was shown by the documents and participate at several levels, from being considered a simple tool or general knowledge, to being part of the program structure, representing a strong basis on which it can be organized, thus contributing in diverse manners to credit load and content. Even in programs in which Physics is not too present, it performs a role of great importance, offering conditions for scientific, technical and technological comprehension to the students, enabling the establishment of fundamental thoughts for both academic and professional comprehensions, as well as private and social.